Craft-Therapy Hub: Pemberdayaan Ekonomi Kreatif dan Digitalisasi Usaha Anggota Prolanis - Injilia W.G Wua; Francisca Anggun Therok; Durand Fernandito; Lidya D.P Canon; Imam Santoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
This community service program aims to empower 25 members of the Chronic Disease Management Program (Prolanis) at Puskesmas Bailang, Manado—primarily patients with type 2 diabetes mellitus and hypertension—through an integrated program called the